Literacy and Art: Collage for Pre-Service Teachers - Alice J. Feret; Judith J. Smith (Park University, 2010)
Art educators have a unique opportunity to develop and strengthen a crosscurricular foundation in literacy through art education. Enrolled in a content area reading course, pre-service teachers in art education at one, large southeastern university discovered that using language skills as a lens sharpened their observations of student performance in art classes at the elementary and high school levels. The inclusion of brief lessons featuring listening, reading, speaking, or writing strategies revealed unanticipated academic needs, which impacted classroom performance and artistic development. This increased awareness deepened preservice teachers' understanding of young students as learners and allowed the preservice teachers to adjust their lesson planning and classroom management skills. The pre-service teachers were more confident in their practice as they witnessed the results of their efforts in terms of students' improved levels of artistic achievements.